CIKS (Act1 or TRAF3IP2) mediates high glucose-induced endothelial dysfunction - Venkatesan, Balachandar (2012)
Hyperglycemia-induced endothelial dysfunction is characterized by enhanced inflammatory cytokine and adhesion molecule expression, and endothelial-monocyte adhesion. The adapter molecule CIKS (connection to IKK and SAPK/JNK; also known as Act1 or TRAF3IP2) mediates NF-κB and AP-1 activation, and plays a role in inflammation and injury. Here we show that high glucose- (HG; 25 mM vs. 5 mM D-glucose)-induced endothelial-monocyte adhesion and inhibition of endothelial cell (EC) migration were both reversed by CIKS knockdown. In EC, HG induced CIKS mRNA and protein expression via DPI-inhibitable Nox4-dependent ROS generation. Further, HG induced CIKS transcription and enhanced CIKS promoter-dependent reporter gene activation via Nox4, ROS, AP-1 and C/EBP. Coimmunoprecipitation and immunoblotting revealed CIKS/IKKβ/JNK physical association under basal conditions that was enhanced by HG treatment. Importantly, CIKS knockdown inhibited HG-induced (i) IKKβ and JNK phosphorylation, (ii) p65 and c-Jun nuclear translocation, (iii) NF-κB- and AP-1-dependent proinflammatory cytokine, chemokine, and adhesion molecule expression. Similar to HG, the deleterious metabolic products of chronic hyperglycemia, AGE-HSA, AOPPs-HSA and oxLDL, also induced CIKS-dependent endothelial dysfunction. Notably, aortas from streptozotocin-induced and the autoimmune type 1 diabetic NOD and Akita mice showed enhanced DPI-inhibitable ROS generation and CIKS expression. Since CIKS mediates high glucose-induced NF-κB and AP-1-dependent inflammatory signaling and endothelial dysfunction, targeting CIKS may delay progression of vascular diseases during diabetes mellitus and atherosclerosis.